Pengaruh Pestisida Nabati Daun Ketepeng Cina (Cassia alata linn.) Terhadap Mortalitas Hama Wereng Batang Coklat (Nilapavarta lugens stal.) Pada Tanaman Padi - Astuti, wahyu puji; Aidawati, Noor; Liestiany, Elly (www.ulm.ac.id, 2025)
One of the causes of decreased production of rice plants is the attack of pests caused by the brown planthopper (Nilapavarta lugens Stal.). This study aims to determine the effect of the botanical pesticide Chinese ketepeng leaves (Cassia alata L.) on the mortality of brown planthopper pests (N. lugens Stal.) on rice plants. The method used in this research was the RAL (Completely Randomized Design) method with one factor, namely the concentration of botanical pesticides, consisting of 6 treatments with 4 replications, and having 24 experimental units in the form of a water solution as a negative control, a synthetic pesticide solution as a positive control and concentrations of Chinese ketepeng leaf solution of 10, 30, 50 and 70%. The data analysis technique uses the Least Significant Difference Test (BNT/LSD) at a significance level of 5%. The results show that the botanical pesticide solution derived from the leaves of Chinese ketepeng (C. alata L.) can cause death (mortality) in the brown planthopper (N. lugens Stal.). During 336 hours or 14 days of observation, the death rate of brown planthoppers due to the vegetable pesticide Chinese ketepeng leaves at concentrations of 10, 30, 50 and 70% was 31.67, 46.67, 51.67 and 68.33% respectively. LC50 (Lethal Concentration 50%) with a mortality value of 68.574% in the dose range of 50 to 70% and the results of the LT50 (Lethal time) probit showed that the T4 treatment showed the fastest LT50, namely 192.512 hours in killing 50% of the brown planthopper nymphs.